English Summary Writing Instruction: Boosting Students' Achievement with Collaborative Strategies (2023)
The study determined the effects of reciprocal teaching and direct reading and thinking activities strategies on English summary achievement of 300 SSII students in six intact classes in senior secondary schools in Iwo, Osun State, Nigeria. Three hypotheses were tested at 0.05 level of significance. English Summary Achievement Test (r=0.87) and instructional guide were the instruments for data collection. Treatment lasted six weeks. Findings revealed that the two strategies improved students achievement in English summary writing, but gender had no significant main and interaction effects on achievement.Teachers of English are enjoined to adopt both strategies in teaching English summary writing.